Упростите выражение 1) (x+1)(x-1)-(x+5)(x-5)+(x+1)(x-5) 2) 81a^8-(3a^2-b^3)(9a^4+b^6)(3a^2+b^3) Помогите пожалуйста

Упростите выражение 1) (x+1)(x-1)-(x+5)(x-5)+(x+1)(x-5) 2) 81a^8-(3a^2-b^3)(9a^4+b^6)(3a^2+b^3) Помогите пожалуйста
Гость
Ответ(ы) на вопрос:
Гость
(x+1)(x-1)-(x+5)(x-5)+(x+1)(x-5)=x^2-1-x^2+25+x^2-5x+x-5=x^2-4x+19 81a^8-(3a^2-b^3)(9a^4+b^6)(3a^2+b^3)==81a^8-(9a^4-b^6)(9a^4+b^6)=81a^8-81a^8+b^12=b^12
Гость
1) = х^2-1-х^2+25+х^2-4х-5=х^2-4х+19=(х-2)^2+15 2)81а^8-(9а^4+b^6)(9a^4-b^6)=81a^8-81a^8+b^12=b^12
Не нашли ответ?
Ответить на вопрос
Похожие вопросы